Analysis of the Factors Contributing to High School Dropout Rates (A Review from the Perspective of Educational Management) - Prima Hadi; Wiwik Wijayanti; Mada Sutapa (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
The high dropout rate remains a serious challenge in educational development due to the complexity of social, economic, psychological, and educational governance factors influencing it. This study aims to analyze the factors causing school dropouts from the perspective of educational management and to evaluate the effectiveness of school governance in preventing dropout cases. The study employed a qualitative approach with an interpretive paradigm and a case study design. Data were collected through in-depth interviews, observations, documentation, and school archive studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña through data reduction, data display, thematic coding, and conclusion drawing. The findings indicate that family economic conditions, low learning motivation, weak family support, psychological pressure, social environment, and limited access to education are the dominant factors contributing to school dropouts. From the educational management perspective, student monitoring, counseling services, and early dropout detection systems have not been implemented optimally or sustainably. The study concludes that strengthening student retention-based educational governance, preventive counseling services, and collaboration among schools, families, and communities are essential strategies for sustainably reducing dropout rates.